Exploring public attitude toward biofeedback technologies: Knowledge, preferences and personality tendencies - Gaetano A. Russo; Serena Oliveri; Clizia Cincidda; Paolo Guiddi; Gabriella Pravettoni (SAGE Publishing, 2020)
Background: Biofeedback is increasingly used in the clinical area and in daily health monitoring through wearable devices (e.g. smart watches). Nevertheless, it remains rather unknown. This study aimed to assess, in a sample of Italian citizens, the level of knowledge, attitudes, perceived efficacy and personality tendencies which could affect the uptake of biofeedback technologies.  Design and Methods: Participants were recruited by advertising the survey on the social networks, from March to May 2019. 160 subjects filled in an ad hoc online questionnaire assessing socio-demographic variables, clinical status, physical activity, knowledge and attitude towards biofeedback, psychological tendencies toward health. Results: Data showed a good level of interest in biofeedback training in spite of poor knowledge about such technologies. Sport and chronic diseases were not correlated to a greater use of biofeedback. People informed about biofeedback technologies were more interested in undergoing biofeedback training and had higher scores in the Health Locus of Control. Finally, people who showed a positive perception of their own health (Health Esteem) did not rely on these technologies. Discussion: Despite the huge spread of biofeedback technologies, our results disconfirmed the expectation that people having an active lifestyle or a disease were more familiar with biofeedback systems. The attitude toward such technologies seems to depend on individual tendencies. Conclusions: This study suggests the importance to improve general public literacy on biofeedback technologies, tailor tools on their needs and characteristics, empower people's sense of internal health control for promoting a valid use and a proper knowledge of biofeedback.